PEMBERDAYAAN PEREMPUAN MELALUI PELATIHAN PENGOLAHAN MAKANAN UNTUK MENGATASI STUNTING BALITA DI DAERAH PERDESAAN - Tri Siswati; Sabrina Nur Afiati; I Made Alit Gunawan (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2022)
Stunting is global malnutrition problem. The adequate consumption is essential determinants of children malnourish. Women's empowerment is an important strategy to improve nutritional status of underfive children. This research was to determine the effectiveness of empowering mothers to increase knowledge, attitude, and skill of providing healthy food. This was an experimental study with pre-post test design. The located was in rural locus stunting areas in Kulon Progo on 2019. Women empowerment was provided by three days training about stunting and providing healthy food for stunting children. The dependent variable were knowledge, attitude and practise were observed by a structure questionnaire pre and post-intervention and check list. Subjects were 30 mothers who consenting to be participant. Data pre-post test of knowledge and attitude were analyzed by Wilcoxon test. Result showed that knowledge and attitudes increased by 9.7 and 14.3 point respectively and statistically significant. While after intervention as many as 80% mothers has excellent skills on providing healthy food for stunting children. In general this research increases knowledge and attitudes of mother’s, also edvancing skill on providing healthy food for improving nutritional children.